THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT METSKY DINE & LOUNGE BEKASI - Riani P. Ishak; Nisa Rahmaniyah Utami (JELAJAH: Journal of Tourism and Hospitality, 2022)
The purpose of this study was to determine and analyze the effect of service quality on customer satisfaction at Metsky Dine & Lounge Bekasi. This research uses descriptive research with a quantitative approach and simple linear regression analysis method. The sampling technique uses accidental sampling. The population is all customers who come to Metsky Dine & Lounge Bekasi, while the total sample is 100 respondents based on the Slovin formula. The results showed that the service quality variable has an effect on customer satisfaction at the Metsky Dine & Lounge Bekasi restaurant. It is hoped that Metsky Dine & Lounge Bekasi will continue to maintain and improve their service quality so customers continue to feel satisfied.